Incorporation of Opuntia macrorhiza Engelm. in cake-making: Physical and sensory characteristics. (April 2018) - Chahdoura, Hassiba; Chaouch, Mohamed Aymen; Chouchéne, Wiem; Chahed, Adel; Achour, Sami; Adouni, Khawla; Mosbah, Habib; Majdoub, Hatem; Flamini, Guido; Achour, Lotfi
Abstract: Nowadays, it has been an increasing demand for health-oriented products such as high fiber and low calories products. The aim of this work is to try to substitute these additives with a natural extract from Opuntia macrorhiza Engelm. which is a good source of dietary fibre and mineral compounds. Physicochemical and functional properties of seeds and cladodes powders were investigated and indicated the possibility of incorporating them into the manufacture of cakes. The study demonstrated that cakes having good sensory qualities can be produced by the replacement of wheat flour with 15% of cladodes and 5% of seeds powder. The consumption of a cake enriched with O. macrorhiza cladodes and seeds is also proposed for health reasons. Thus, the flour obtained from O. macrorhiza cladodes and seeds can be suggested as an ingredient in food products. Highlights: Physicochemical and functional properties of Opuntia macrorhiza Engelm seeds and cladodes were determined. Effect of cladodes and seeds powders on the rheological properties of dough and the quality of cakes. Cakes containing cladodes and seeds powders had better physical characteristics. The overall acceptability rate showed that a cake with 15% of cladodes and 5% seeds powders was acceptable. Cladodes and seeds powders could be a good substitution of wheat flour.